2018
DOI: 10.3389/fpls.2018.01059
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of a Novel Heading Date Gene, TaHdm605, in Hexaploid Wheat

Abstract: The heading date is critical in determining the adaptability of plants to specific natural environments. Molecular characterization of the wheat genes that regulate heading not only enhances our understanding of the mechanisms underlying wheat heading regulation but also benefits wheat breeding programs by improving heading phenotypes. In this study, we characterized a late heading date mutant, m605, obtained by ethyl methanesulfonate (EMS) mutation. Compared with its wild-type parent, YZ4110, m605 was at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…One of important agronomic traits of rice is heading dates, which is related to the attributes of regional adaptability and yield. 18 DJ is a mid-to-late flowering rice cultivar that is generally cultivated in the Korean peninsula (Southern plain region, 33°–44° N latitude). Based on the results, mid-to-late August, which is the summer season in Korea, is suitable for heading of both DJ and I526 rice.…”
Section: Discussionmentioning
confidence: 99%
“…One of important agronomic traits of rice is heading dates, which is related to the attributes of regional adaptability and yield. 18 DJ is a mid-to-late flowering rice cultivar that is generally cultivated in the Korean peninsula (Southern plain region, 33°–44° N latitude). Based on the results, mid-to-late August, which is the summer season in Korea, is suitable for heading of both DJ and I526 rice.…”
Section: Discussionmentioning
confidence: 99%
“…m605 is a late heading mutant that was identified from the ethyl methanesulfonate mutant library of YZ4110. Previous studies conducted in our laboratory identified m605 as a late heading mutant compared with its wild type parent YZ4110 [ 32 ]. To reveal the flowering time regulation model of genes for the heading date, homozygotes for the early heading date (WHd) and late heading date phenotype (MHd) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Plant materials m605 is a late heading mutant that was identi ed from the ethyl methanesulfonate mutant library of YZ4110. Previous studies conducted in our laboratory identi ed m605 as a late heading mutant compared with its wild-type parent YZ4110 [32]. To reveal the molecular mechanism of the genes that regulate the heading date, backcrossed BC 3 F 4 progeny of YZ4110 × m605 was subjected to RNA-seq analysis, and the purpose of using the backcrossed segregating population was to reduce the false positive problems caused by the genetic background.…”
Section: Methodsmentioning
confidence: 99%